2016
DOI: 10.1016/j.jvs.2016.03.463
|View full text |Cite
|
Sign up to set email alerts
|

Use of hyperspectral imaging to assess endothelial dysfunction in peripheral arterial disease

Abstract: Our study suggests the ability of HSI to assess the presence of PAD or CAD based on systemic vascular dysfunction at sites remote from the clinically diseased vascular bed. This could enable early screening and tracking of arterial disease patients before the development of clinically advanced disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 38 publications
(56 reference statements)
1
12
0
Order By: Relevance
“…The clinical use of this technique has been previously investigated in patients with cervical cancer and skin cancer as well as in an application for lower extremity perfusion measurements [11]. Previous studies determined superficial tissue oxygenation with HSI in patients with PAOD and diabetes mellitus (DM) and showed an association with severity of disease and wound healing [12][13][14][15]. Chin et al showed that lower values of DeoxyHb were associated with peripheral arterial disease, and that DeoxyHb values correlated with ABI [16].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical use of this technique has been previously investigated in patients with cervical cancer and skin cancer as well as in an application for lower extremity perfusion measurements [11]. Previous studies determined superficial tissue oxygenation with HSI in patients with PAOD and diabetes mellitus (DM) and showed an association with severity of disease and wound healing [12][13][14][15]. Chin et al showed that lower values of DeoxyHb were associated with peripheral arterial disease, and that DeoxyHb values correlated with ABI [16].…”
Section: Introductionmentioning
confidence: 99%
“…5 The HTCOM device has been used to evaluate endothelial function in vascular patients in a recent publication by Sumpio et al, which demonstrated the ability of this technology to potentially assess and screen for the presence of PVD. 6 The OxyVu (HyperMed Inc, Burlington, Mass) is a mobile HTCOM system that noninvasively obtains information from the subpapillary plexus by detecting the presence of chromophores that are uniquely specific to oxyhemoglobin (HT-Oxy) and deoxyhemoglobin (HT-Deoxy). 7 Using a "target," that is, a small sticker that measures a standard surface area of 204 mm 2 placed at the region of interest, the mounted camera produces light at various wavelengths that penetrates the skin to a depth of 1 to 2 mm.…”
mentioning
confidence: 99%
“…This study had a unique design and unique findings compared to previous studies that used SWIR light HSI as a clinical diagnostic technique [17,46,48]. Our study used the HSI technique to identify early-stage disease with invisible skin changes.…”
Section: Discussionmentioning
confidence: 99%